Performance indicators of broilers fed propolis and bee pollen additive - Prakatur, Ivana (Array, 2019)
The aim of this study was to determine the effect of diet supplementation with propolis and/or bee pollen on the performance indicators of broilers. This experimental study was conducted on 200 Ross 308 broilers equally distributed by sex and divided into five groups. Throughout the whole study the control group of chickens was fed feed mixture. Feed mixture fed to the experimental groups of chickens contained additives (propolis and/or bee pollen, each supplement separately or in combination in a certain proportion). The average values of broilers body weight were significantly higher on 7th (p=0.001), 14th, 21st, 28th, 35th (p<0.001) and 42nd (p=0.002) day of feeding in the experimental groups of broilers compared to the control group. The average values of broilers weight gain were significantly higher on 1st (p<0.001), 2nd (p=0.002), 3rd (p<0.001), 4th (p=0.029) and 5th (p=0.009) week of feeding in the experimental groups of broilers compared to the control group. This study has undoubtedly shown that propolis and bee pollen have significant positive effect on performance indicators of broilers.